2014
DOI: 10.1039/c3ce41692e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal route to metastable phase FeVO4ultrathin nanosheets with exposed {010} facets: synthesis, photocatalysis and gas-sensing

Abstract: In this paper, pure metastable phase iron vanadate (FeVO 4 -II) ultrathin nanosheets (50 nm in thickness) with exposed {010} facets were obtained by a mild hydrothermal process, without the use of any template or organic surfactant. The photocatalytic rate of the FeVO 4 -II {010} facets was measured taking advantage of their unique morphology. Furthermore, the FeVO 4 -II catalyst could be easily separated and reused, simply by applying an external magnetic field. In addition, with their n-type semiconductor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…6b), respectively, which correspond to the characteristics of V 5+ , identical to previous reports (V2p peak positions of V 5+ are at 517 ± 0.1 eV and 525 ± 0.1 eV) [24,25]. [35].…”
Section: Morphology and Compositionsupporting
confidence: 69%
See 3 more Smart Citations
“…6b), respectively, which correspond to the characteristics of V 5+ , identical to previous reports (V2p peak positions of V 5+ are at 517 ± 0.1 eV and 525 ± 0.1 eV) [24,25]. [35].…”
Section: Morphology and Compositionsupporting
confidence: 69%
“…In addition, from Fig. 6c, it can be observed that the O1s peak of pure FeVO 4 nanorods is located at a binding energy of 530.58 eV, whereas for Pt-decorated FeVO 4 nanorods, the O1s peak is located at a slightly higher binding energy of 530.78 eV, which resulted from the noble metal-oxide support interaction [24,25]. The high resolution O1s XPS profile of the Pt-decorated FeVO 4 nanorods contains several peaks.…”
Section: Morphology and Compositionmentioning
confidence: 88%
See 2 more Smart Citations
“…Great efforts have been paid to synthesize many vanadates (such as InVO 4 , BiVO 4 , CeVO 4 , Ag 3 VO 4 , Ag 2 V 4 O 11 , AgVO 3 , Mg 3 (VO 4 ) 2 , Zn 3 (VO 4 ) 2 , FeVO 4 , and LaVO 4 ) and study their photocatalytic activity [20][21][22][23][24][25][26][27][28][29][30]. However, the low photocatalytic activity of pure vanadates restricts its wide application in the photocatalytic degradation of organic contaminants owing to its poor adsorptive performance and the difficulty of migrating photogenerated electron-hole pairs.…”
Section: Introductionmentioning
confidence: 99%